Pendampingan Pembelajaran Online Menggunakan Edmodo bagi Siswa Kelas 9 SMP Muhammadiyah 6 Semarang - Yani Parti Astuti; Egia Rosi Subhiyakto; Liya Umaroh (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2021)
In education, students have a very important role for schools. Creative and innovative students will bring good name and progress to the school. For this reason, besides getting formal education, students must make optimal use of technology. So that every student is able to compete with the outside world and have an established provision to continue their education to a higher level. Given the current situation where the world is confused with the Covid-19 pandemic outbreak, school students are also recognized by the existence of an education system from home. Education from home does not mean students only learn themselves, but students are expected to be able to work with teachers and other students using the internet. This system is called e-learning or educational media with the internet. In fact, many students do not understand e-learning, especially junior high school students. The school that is the object of the Community Partnership Program (PKM) in the context of community service is SMP Muhammadiyah 6 Semarang, having its address at Jl. Brotojoyo II no 22, Panggung Kidul Kec. North Semarang Semarang. This service is expected to provide understanding and assistance in implementing e-Learning using edmodo for students of SMP Muhammadiyah 6 Semarang. And finally it can create more interactive learning and can increase student motivation..